The Pre- and Postoperative FIB-4 Indexes Are Good Predictors to the Outcomes of HBV-Related HCC Patients after Resection. (1st December 2019) - Tsai, Meng-Yun; Yen, Yi-Hao; Huang, Pao-Yuan; Sou, Fai-Meng; Lin, Chih-Che; Cho, Wei-Ru; Wang, Hsin-Ming; Chen, Ding-Wei; Chang, Kuo-Chin; Wu, Cheng-Kun; Hu, Tsung-Hui; Tsai, Ming-Chao
Abstract : Background and Aim . Liver fibrosis is associated with the prognosis of patients with hepatocellular carcinoma (HCC) after resection. The fibrosis-4 (FIB-4) index is an accurate and noninvasive marker to determine the degree of liver fibrosis. Here, we evaluated the effect of pre- and postoperative FIB-4 index in predicting the outcomes after resection of HCC in patients who have chronic hepatitis B (CHB) infection. Methods . A total of 534 CHB patients with HCC who received curative hepatectomy between 2001 and 2016 at Kaohsiung Chang Gung Memorial Hospital, Taiwan, were enrolled in this study. The impact of the FIB-4 index (preoperative and the 1 st year after operation) on overall survival (OS) and recurrence-free survival (RFS) was evaluated. Results . There was a significant association between the preoperative FIB-4 index and Metavir fibrosis stage (p < 0.01 ). The multivariate analysis showed that preoperative FIB ‐ 4 > 2 is an independent risk factor for RFS and OS after HCC curative resection [hazard ratio (HR), 1.902; 95% CI, 1.491–2.460; p < 0.001, and HR, 2.207; 95% CI, 1.420–3.429; p < 0.001, respectively]. Notably, preoperative FIB-4 is also an independent risk factor for RFS (HR, 1.219; p = 0.035 ) in noncirrhotic patients. Furthermore, patients had deteriorated FIB-4 1 year after operation [definition: the value the 1 st year FIB ‐ 4 after operation minus preoperative FIB ‐ 4 > 1 ] and had an adverse outcome in RFS and OS (p < 0.001, both). Conclusion . The pre and postoperative FIB-4 indexes are useful clinical markers to predict the prognosis in HBV-HCC patients after curative hepatectomy.